The Challenges of Religious Harmony and Tolerance in Developing Countries - Sari, Anggun Putri Indah (Faculty of Law, Universitas Negeri Semarang, 2022)
This study aims to analyze how the challenges of religious harmony and tolerance in Indonesia are in the social and legal aspects. This study uses a literature study approach by comparing several legal regulations and previous research related to secondary data. This study found that religious harmony is a state of inter-religious relations based on tolerance, mutual understanding, mutual respect, respect for equality in the practice of their religious teachings and cooperation in social, national and state life within the Republic of Indonesia based on Pancasila and the 1945 Constitution of Indonesia. The right to religion (to embrace and practice worship) guaranteed by the Constitution and other laws is not a right that can be exercised at will. This means that there are certain signs or conditions so that the exercise of that right does not interfere with the rights of other people, the security and order of the community, the state and the nation; in other words, there are restrictions that must be considered by residents. This limitation is in Article 28J paragraph (2) of the 1945 Constitution in conjunction with Article 73 of the Human Rights Law. Article 28J paragraph (2) stipulates that in exercising their rights and freedoms, everyone is obliged to comply with the restrictions determined by law with the sole purpose of guaranteeing recognition and respect for the rights and freedoms of others and to fulfill fair demands in accordance with moral considerations, religious values, security, and public order in a democratic society.